Endoscopic diagnosis of gastric intestinal metaplasia: A prospective multicenter study. Issue 5 (29th January 2013) - Fukuta, Nobuhiro; Ida, Kazunori; Kato, Takahiro; Uedo, Noriya; Ando, Takashi; Watanabe, Hidenobu; Shimbo, Takuro
Abstract : Background: Intestinal metaplasia (IM) of the gastric mucosa has long attracted attention as a premalignant lesion involved in gastric carcinogenesis. However, endoscopic diagnosis of IM has remained unclear for a long time. In recent years, the methylene blue staining technique and narrow‐band imaging (NBI) magnifying endoscopy have facilitated clinical diagnosis of IM, although these methods have some problems due to their complexity. Simple methods for diagnosis of IM using conventional endoscopy and the indigo carmine contrast (IC) method are necessary. Patients and Methods: This study was a multicenter, prospective, randomized, comparative study involving 10 facilities. The appearance of IM was examined using conventional and IC methods with an electronic endoscope. Results: Subjects included 163 patients, of whom 87 and 76 underwent conventional and IC methods, respectively. Sensitivity, specificity, and receiver operating characteristic/area under thecurve (ROC/AUC) of conventional and IC methods for the detection of IM in the gastric antrum showed that diagnostic performance of the conventional method was higher, but not significantly, than that of the IC method. Sensitivity, specificity and ROC/AUC of conventional and IC methods for the detection of IM in the gastric body showed that the IC method yielded better (but not significantly better) results than the conventional method. Conclusion: The diagnostic performance of the conventional method did not significantly differ from that of the IC method. A villous appearance, whitish mucosa, and rough mucosal surface, as observed by both methods, and areae gastricae pattern, as observed by the IC method, were useful indicators for endoscopic diagnosis of IM.